Cane Toad Skin Extract—Induced Upregulation and Increased Interaction of Serotonin 2A and D2 Receptors via Gq/11 Signaling Pathway in CLU213 Cells. Issue 5 (5th January 2017) - Zulfiker, Abu Hasanat Md.; Hashimi, Saeed M.; Good, David A.; Grice, I. Darren; Wei, Ming Q.
ABSTRACT: Recent evidences show that activation of serotonin 2A receptors (5‐HT2A R) by agonists is significant in improving therapeutic activity of disease conditions, such as obsessive‐compulsive disorder (OCD). Though the exact molecular mechanism is still not well understood, it is thought to involve agonist‐driven, enhanced expression of 5‐HT2A R in certain areas of brain, such as the pre‐frontal cortex (PFC). Several other reports have also demonstrated association of OCD with lower dopamine receptor (D2 R) availability, primarily in the striatum of the brain along with dysfunction of 5‐HT2A R‐D2 R heteromer regulation. We thus hypothesized that compound(s) interacting with this molecular mechanism could be developed as drugs for long‐term beneficial effects against OCD. In the present study, we have obtained experimental evidence in cultured neuronal cells (CLU213) that aqueous extract (AE, 50 μg/mL, P  < 0.05) of the Australian cane toad skin significantly increased the levels of 5‐HT2A R and D2 R protein and mRNA expression. AE was also found to enhance the interaction between 5‐HT2A R and D2 R and formation of expression of 5‐HT2A R‐D2 R heteromer using co‐immunoprecipitation and Western blot. Further investigation showed the involvement of classical signaling pathway (Gq/11 ‐PLCβ) along with c‐FOS transcription factor preferentially in 5‐HT2A ‐mediated agonist activation. These results obtained demonstrated that AE upregulates 5‐HT2A R by a mechanism that appears to involve Gq/11 ‐PLCβ signaling pathway and c‐FOS transcription factor activation. We indicate this enhanced 5‐HT2A R and D2 R expression and their interaction to induce increased 5‐HT2A R‐D2 R heteromer formation by exposure to AE might provide a molecular mechanism to develop potential novel drug candidates to ameliorate OCD symptoms. J. Cell. Biochem. 118: 979–993, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Aqueous extracts (AE) of Australian cane toad skins induce upregulation of 5‐HT2A and D2 receptos and enhance their interaction in a neuronal cell (CLU213) in vitro via Gq/11 G‐protein PLCβ signaling pathway and c‐FOS transcription factor activation. This could provide a molecular mechanism to develop AE of Australian cane toad skins as potential novel drug candidates to ameliorate OCD symptoms.